KETERAMPILAN BERSUCI SISWA MELALUI PEMAHAMAN MATERI THAHARAHKELAS VII MTS. WAHID HASYIM 01 DAU MALANG - Imroatul Arifah; Ika Ratih Sulistiani; Mohammad Afifulloh (VICRATINA, 2019)
This study aims to determine purification skills of grade VII through understanding thaharah material at MTs. Wahid Hasyim 01 Dau Malang. The problem faced is that there are some students who do not maintain the sanctity of clothing for prayer and ablution is not perfect.Tthis will inhibit the formation of purification skills that make students able to carry out purification activities easily, precisely, and perfectly in accordance with Shari'a in everyday life. This study uses a qualitative method, where documents is obtained based on the results of interviews, observation, and documentation. Which is analyzed by documents reduction, documents presentation, drawing conclusions. The results of this study indicatr that the teacher uses several strategies that have been designed and applied using the Fiqh teacher uses habituation methods and supervision that support the formation of purification skills for students. Keywords: thaharah, skill of thaharah